The role of socio-emotional security on school engagement and academic achievement: systematic literature review - Dias, Pedro (2024)
Introduction: Socio-emotional security and particularly secure attachment relationships with parents and peers have been associated with positive developmental outcomes, including school-related variables. This systematic literature review aims to provide a comprehensive analysis of the literature, exploring the relationship between socio-emotional security (attachment, support, and secure relations with parents and peers) and academic achievement, school engagement, and early school dropout. Methods: The inclusion criteria were studies with socio-emotional security as the independent variable and academic achievement and/or school engagement as the dependent variable, using a quantitative methodology, written in English. The exclusion criteria were articles presenting literature review or meta-analysis, interventions or instrument validation studies, studies with a qualitative approach, studies developed in an e-learning context, studies with university students, and/or focused on schooling in extreme conditions (e.g., COVID-19). PRISMA guidelines were followed, through a search that resulted in the identification of 38 empirical quantitative studies, published between 2018 and 2022, in English. Results and discussion: The results revealed that parent and peer relationships impact students’ academic achievement and school engagement, as expected, and highlighted the relevance of parental and peer relationships for school-related outcomes. Future research should consider the role of potential mediators and moderators in the relationship between socio-emotional security and school outcomes.